2010
DOI: 10.1152/jn.90937.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Ventrolateral Prefrontal Cortex Involvement in Memory Formation

Abstract: Human neuroimaging studies have implicated a number of brain regions in long-term memory formation. Foremost among these is ventrolateral prefrontal cortex. Here, we used double-pulse transcranial magnetic stimulation (TMS) to assess whether the contribution of this part of cortex is crucial for laying down new memories and, if so, to examine the time course of this process. Healthy adult volunteers performed an incidental encoding task (living/nonliving judgments) on sequences of words. In separate series, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 66 publications
(147 reference statements)
3
34
0
Order By: Relevance
“…Taken together, the studies by Machizawa et al (2010) and Rossi et al (2011) have provided evidence that post-stimulus brain activity plays a role in memory formation.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Taken together, the studies by Machizawa et al (2010) and Rossi et al (2011) have provided evidence that post-stimulus brain activity plays a role in memory formation.…”
Section: Introductionmentioning
confidence: 77%
“…Several event-related functional magnetic resonance imaging (fMRI) and electroencephalographic (EEG) studies used this approach to reveal the network of brain regions implicated in successful memory formation (for early reviews, Friedman & Johnson, 2000;Paller & Wagner, 2002). More recently, non-invasive brain stimulation techniques (transcranial magnetic stimulation, TMS; transcranial direct current stimulation, tDCS) added to this literature by showing that the stimulation of selected regions of the prefrontal cortex during memory encoding affected later retrieval (Rossi et al, 2001(Rossi et al, , 2004(Rossi et al, , 2006(Rossi et al, , 2011Köhler, Paus, Buckner & Milner, 2004;Machizawa, Kalla, Walsh & Otten, 2010;Blumenfeld, Lee & D'Esposito, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been consistently demonstrated using various types of stimulation pulses (rTMS, single pulse, pairedpulses) and memory items (word, picture) (Blumenfeld, Lee, & D'Esposito, 2014;Gagnon, Blanchet, Grondin, & Schneider, 2010;Kahn et al, 2005;Machizawa, Kalla, Walsh, & Otten, 2010;Rossi et al, 2001;Sandrini, 2003;Skrdlantová, Horácek, Dockery, Lukavský, & al, 2005).…”
Section: Left Prefrontal Cortex Stimulationmentioning
confidence: 86%
“…Studies in PFC lesion patients have reported impaired performance in free recall (29)(30)(31)(32) and in complex memory tasks like source memory (33) or associative learning (34)(35)(36), but recognition memory impairment after PFC lesions or VLPFC transcranial magnetic stimulation is modest (32,37). These impairments have been attributed to deficits in cognitive control of information selection and organization rather than a primary memory deficit (7).…”
Section: Discussionmentioning
confidence: 99%